Symptoms and Otorhinolaryngological Sequalae in Long Covid - Loli, Alessandra [UNESP]; Müller, João Victor Costa [UNESP]; Azevedo, Eric Schneider De; Martins, Regina Helena Garcia [UNESP] (Thieme, 2025)
Introduction: After the pandemic caused by the coronavirus, many patients have presented remaining otorhinolaryngological symptoms, but most of them are unknown to health professionals. Objectives: To characterize otorhinolaryngological symptoms and sequelae in hospitalized patients for Covid-19. Methods: We made a recall to patients hospitalized between April 2020 and April 2022 due to Covid-19. Demographic data, initial and remaining symptoms, days of hospitalization, intubation and/or tracheostomy, and vaccination data were collected. Results: 845 patients were hospitalized, 441 died, 404 patients were contacted by telephone, but only 109 responded to the questionnaire about initial and remaining otorhinolaryngological symptoms after 1.5 to 2 years of illness, 59 men and 50 women, with an average age of 58.61 years (20 to 94). Two study groups were composed: G 1 (n- 44; with remaining symptoms) and G 2 (n- 65; without remaining symptoms). 81% of patients in G1 and 67% of patients in G2 had been hospitalized for up to 20 days. Intubation occurred in 17 patients (G1-7; G2-10). Seven patients underwent tracheostomy. The most prevalent initial and remaining otorhinolaryngological symptoms, respectively, were dyspnea (68.8%; 14.6%), cough (65.1%; 11.92%), nasal obstruction (47.7%; 5.58%), smell dysfunction (44%; 11%), taste dysfunction (42%; 4.58%). Vaccination was reported by 54 patients (G1-21; G2-34). Conclusions: Otorhinolaryngological symptoms were common in patients hospitalized for Covid-19, especially dyspnea, cough, nasal obstruction, smell, and taste dysfunction. Although there was a favorable long-term evolution, 40% of patients maintained permanent symptoms, such as smell and taste dysfunction and dizziness, unrelated to the vaccine doses.